ANALISIS KESULITAN BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DENGAN METODE ELIMINASI DI SMP NEGERI 4 PANGALENGAN - Soja Rine Sundary; Rippi Maya; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Mathematics has an important role in life. But in the practice of learning mathematics, some students still have the assumption that mathematics is difficult. Some evidence in the field shows that learning outcomes on SPLDV material are still low. The purpose of the study was to analyze the learning difficulties of students, class VIII at SMPN 4 Pangalengan, in solving questions on the SPLDV material, a qualitative descriptive approach was used in this study, the subjects of this study were 10 students of class VIII-D SMPN 4 Pangalengan. The test instrument used was the SPLDV description test with 3 questions, then the students' difficulties were analyzed using qualitative data analysis techniques. Data collection techniques using the test method. The analysis steps include data reduction, data presentation, and verification. The results showed that students' difficulties in learning SPLDV were difficulty understanding the concept of SPLDV, then changing story questions into mathematical form, and using methods in determining the SPLDV completion set and difficulties understanding supporting material.